IMPLEMENTASI PROGRAM PARIWISATA DALAM MENINGKATKAN DESTINASI WISATA DI KABUPATEN JOMBANG - Novaria, Rachmawati (DIA: Jurnal Administrasi Publik, 2017)
Tourism is the potential of each region, with the optimal management of the tourism sector is able to improve the economic growth of surrounding communities. In response to the problem of managing the tourismÂ  sector, not only the government that is responsible, but the role of private and public sectors is needed which is run according to the tourism program in Jombang. The tourism problem Jombang much frequented by foreign tourism and domestic tourist and increase from year but no significant impact on revenue. This study uses data collection techniques interviews and documentation. Technical analysis of the data used include qualitative data analysis. The result of this study refers to the theory of Van Meter and Van Horn as a confirmationÂ  of the theory. This study found that tourism program Jombang is not optimal, the number of tourist who visit do not have an impact on increasing revenue for local government. It was also found not optimal implementation of tourism programs implemented. Tourism policy by applying the model of information system integrated tourism (integrated tourism/IT) can be synergized and integrated toursm development program that is ideal in these destinations and the socialization of program / tourism activities be intensified and evenly to the surrounding community to express their aspirations so that this cooperation can goes well and provide benefits to all and teint parties. eg travel agents, transportation, hotels, catering, tour operators, tour operators, tourist attraction and souvenir shop, where everything is together teintergrasi it will have an impact on increase in tourist destinations and revenue.